Factors associated with the occurrence of upright birth in Brazil - Carlos Martins Neto; Cleber Lopes Campelo; Janielle Ferreira de Brito Lima; Karla Danielle Silva Marques Mendes; Leandro Saldanha Nunes Mouzinho; Alcione Miranda dos Santos; Erika Barbara Abreu Fonseca Thomaz (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To identify the factors associated with Upright Delivery (UD) performed in hospitals linked to the Rede Cegonha (RC) in Brazil. Methods: Cross-sectional study with 3,073 parturients who had vaginal delivery in 606 health facilities in Brazil, located in health regions with a regional action plan approved in the RC. Socioeconomic, demographic, and obstetric characteristics of the parturients, organizational and management aspects of maternity hospitals, and work processes in childbirth care were evaluated. The multivariate logistic regression model with a hierarchical approach was adjusted to identify the variables associated with UD (outcome), estimating Odds Ratios (OR) with a significance level of 5%. Results: Of the evaluated parturient, 6.7% gave birth in the vertical position. The following were associated with a greater chance of PPV: being black (OR=2.07); having 13 or more years of study (OR=3.20); giving birth in a high-risk hospital (OR=1.58); giving birth in PPP rooms (which assisted with labor, delivery, and puerperium in the same environment) in Obstetric Centers (OR=2.07) or in-hospital Normal Delivery Centers (OR=1.62); being assisted by an obstetrician nurse (OR=1.64) or by a midwife (OR=7.62) when compared to a doctor; receiving massage during labor and delivery (OR=1.89); using a stool (OR=4.16) and among women who did not ask for/not receive analgesia (OR=3.15). Conclusion: The UD is an event related to racial aspects and the education of the parturient, being stimulated in health establishments where good practices of childbirth care are implemented, with adequate ambiance, and with multidisciplinary teams comprising midwives and obstetric nurses.